CONCENTRATION OF HEAVY METAL CADMIUM (Cd) IN BLUE SWIMMING CRAB (Portunus pelagicus) AND IN THE BRACKISHWATER PONDS OF MANGUNHARJO, SEMARANG (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Cadmium (Cd) in the waters considered as one of the pollutants that potentially pollute the waters and contaminating the aquatic biota. The heavy metal cadmium commonly comes from the industrial waste, agriculture, and also other human activities as found around the pond waters of Mangunharjo, Semarang. The purpose of this study was to analyze the cadmium content in sediment and water as well as the Blue swimming crabs (Portunus pelagicus) found in Mangunharjo pond waters. This research was held from December 2020 to January 2021. Measurement of Cadmium concentration was analyzed by the Atomic Absorption Spectrophotometer (AAS) method. The results showed the contamination of heavy metal Cadmium in water measured at